Supernova 2013fc in a circumnuclear ring of a luminous infrared galaxy: the big brother of SN 1998S - T. Kangas; S. Mattila; E. Kankare; P. Lundqvist; P. Väisänen; M. Childress; G. Pignata; C. McCully; S. Valenti; J. Vinkó; A. Pastorello; N. Elias-Rosa; et al. (Oxford University Press, 2025)
We present photometric and spectroscopic observations of SN 2013fc, a bright type II supernova (SN) in a circumnuclear star-forming ring in the luminous infrared galaxy ESO 154-G010, observed as part of the Public ESO Spectroscopic Survey of Transient Objects. SN 2013fc is both photometrically and spectroscopically similar to the well-studied type IIn SN 1998S and to the bright type II-L SN 1979C. It exhibits an initial linear decline, followed by a short plateau phase and a tail phase with a decline too fast for 56Co decay with full γ-ray trapping. Initially, the spectrum was blue and featureless. Later on, a strong broad (˜8000 km s-1) H α emission profile became prominent. We apply a STARLIGHT stellar population model fit to the SN location (observed when the SN had faded) to estimate a high extinction of AV = 2.9 ± 0.2 mag and an age of 10_{-2}^{+3} Myr for the underlying cluster. We compare the SN to SNe 1998S and 1979C and discuss its possible progenitor star considering the similarities to these events. With a peak brightness of B = -20.46 ± 0.21 mag, SN 2013fc is 0.9 mag brighter than SN 1998S and of comparable brightness to SN 1979C. We suggest that SN 2013fc was consistent with a massive red supergiant (RSG) progenitor. Recent mass loss probably due to a strong RSG wind created the circumstellar matter illuminated through its interaction with the SN ejecta. We also observe a near-infrared excess, possibly due to newly condensed dust.